Hydrophilic Acrylic versus Polymethylmethacrylate Intraocular Lens Implantation for Pediatric Cataract Surgery: Iraqi Study (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
PurposeTo make a comparison between the primary implantation of the foldable hydrophilic acrylic and the polymethylmethacrylate intraocular lenses of pediatric cataract surgery that generally includes short term complications and visual results.MethodsThis clinical study includes 40 eyes of 31 consecutive patients who aged from 1 to 6 years complaining from unilateral or bilateral, congenital or developmental cataracts. Two kinds of IOLs, including foldable hydrophilic acrylic and PMMA were randomly implanted in the capsular bag during surgery. Primary posterior capsulotomy and anterior vitrectomy were performed in all eyes. Patients were followed up for at least 1 year. Perioperative complications, visual results and refractive errors were compared between the study categories.ResultsIn the study, regarding age, it was 3.2±1.8 years of the hydrophilic acrylic group and 3.7±1.3 years of the PMMA group. Regarding follow up mean period was 19.6±5 (12–28) months. Intraoperative complications don’t occurr in any group. Postoperative uveitis was observed in 2 (10%) eyes in the acrylic group patient versus 5 (25%) eyes in the PMMA group patient (P=0.40). Other postoperative complications include pigment deposition (30%), posterior synechiae formation (10%) and iridocorneal adhesions (10%), were observed only in the PMMA group. Visual outcomes in these groups study were good and comparable and the visual axis was completely clearConclusionIn pediatric eyes in whom lensectomy was doing with the primary posterior capsulotomy and anterior vitrectomy, the comparison between the hydrophilic acrylic IOLs and PMMA IOLs was made including biocompatibility and visual axis. The observation was that hydrophilic acrylic IOLs is less frequent postoperative complications.